A historiographical review of the «Miesięcznik Połocki» journal - Klimovich, Hanna I. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The work for the first time in the Belarusian history of philosophy deals with the creative heritage of authors belonged to the direction of Polotsk neo-scholasticism, which was published on the pages of the Polotsk Jesuit Academy journal «Miesięcznik Połocki». It explores in detail the philosophical problems presented within the journal, the criteria for selecting articles used by the editors, the basic principles that, according to the editors’ vision, the study should comply with. There was reconstructed the program settings constituted the ideological position of thinkers which were used by them for polemics with representatives of other philosophical trends, in particular, with authors worked in the framework of the French and English enlightenment. New names of thinkers – professors and scientists engaged in the study of philosophical problems at the Academy in the period 1818–1820 – are introduced into the scientific circulation in the field of philosophical knowledge.
Keywords: neo-scholasticism; Polotsk neo-scholasticism; Polack Jesuit Academy; Aristotelian thomism; scotism; cartesianism; Enlightenment; «Miesięcznik Połocki»